2002
DOI: 10.1021/ja026400z
|View full text |Cite
|
Sign up to set email alerts
|

Regular Intergrowth in the AFI-Type Crystals:  Influence on the Intracrystalline Adsorbate Distribution As Observed by Interference and FTIR-Microscopy

Abstract: Interference microscopy and FTIR microscopy are applied to study intracrystalline concentration profiles of methanol in CrAPO-5 zeolite crystals. By using both techniques, the high spatial resolution of interference microscopy is complemented by the ability of FTIR spectroscopy to pinpoint adsorbates by their characteristic IR bands. For the first time two-dimensional concentration profiles of an unprecedented quality are reported which show a nonhomogeneous distribution of adsorbate in zeolite crystal under e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
80
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 10 publications
7
80
0
1
Order By: Relevance
“…On heating, the template decomposes accompanied by the formation of light-absorbing and -emitting species. As the accessibility of the porous network in the subunits varies, [29,30] following the template removal process in time enables visualization and reconstruction of the individual building blocks. Recently, the intergrowth structure of similar, though larger, ZSM-5 crystals was revealed in this manner.…”
Section: Resultsmentioning
confidence: 99%
“…On heating, the template decomposes accompanied by the formation of light-absorbing and -emitting species. As the accessibility of the porous network in the subunits varies, [29,30] following the template removal process in time enables visualization and reconstruction of the individual building blocks. Recently, the intergrowth structure of similar, though larger, ZSM-5 crystals was revealed in this manner.…”
Section: Resultsmentioning
confidence: 99%
“…Nonetheless, it should be mentioned that, only recently, Thompho et al 22 have introduced a potential for such silanol groups on a silicalite-1 surface and that future studies should take into account the surface saturation. Another important point with respect to studying a realistic crystal are lattice defects 23 and crystal intergrowth, 24 all of which are not considered in this study but which are very likely be found in real zeolite crystals. From another point of view, this underlines the complementary relationship between experiments and simulations.…”
Section: Methodsmentioning
confidence: 99%
“…The IFM method has been successfully used to study micropore diffusion in a variety of zeolites such as ferrierite [6], CrAPO-5 and SAPO-5 [7][8][9][10] and MFI [11,12]. The measured concentration profiles in these systems have been used to determine whether the diffusion is one-dimensional, two-dimensional or three-dimensional.…”
Section: Introductionmentioning
confidence: 99%